A low-power, low-noise, high-accurate epileptic-seizure detection system for wearable applications. (October 2019) - Tohidi, Mohammad; Madsen, Jens Kargaard; Moradi, Farshad
Abstract: This paper presents a low-power epileptic-seizure-detection-system (ESDS), including an instrumentational-amplifier (IA), a level-detection-ADC (LD-ADC) and frequency-detection-units (FDUs). In the proposed ESDS, by utilizing low-power techniques, and a new mixed-mode detection-system, the power is reduced to 2 μW. Also, by using large input capacitors and a high-pass-filter (HPF), the electrode-offset-voltage (EOV) is rejected. Hence, the supply voltage is reduced without saturating the input transistors. In the IA, by using the choppers, the input-referred-noise is obtained 0.96 μVrms over 0.5–100 Hz. Also, to avoid signal attenuation, an impedance-boosting-loop (IBL) is used to increase the input impedance up to 18.2 GΩ at 10 Hz. After amplifying the EEG signals, the LD-ADC and FDUs are utilized to detect the amplitudes and activities of the EEG signals. In the proposed ESDS, by using a PGA with variable-gain, a LD-ADC with variable sampling-frequency and FDUs with variable reset-time, the sensitivity is increased up to 100% with the latency of 8.8 s. Besides, a compatible ESDS with different low-voltage fast-activity epileptic-seizures is achieved.